Molybdenum isotopic behavior during intense weathering of basalt on Hainan Island, South China. (15th October 2020) - Liu, Jin-Hua; Zhou, Lian; Algeo, Thomas J.; Wang, Xuan-Ce; Wang, Qian; Wang, Yong; Chen, Mu-Long
Abstract: The behavior of molybdenum (Mo) isotopes during chemical weathering was investigated through analysis of saprolite and soil samples from two weathering profiles developed on Neogene basalts of Hainan Island in southern China. The Penglai and Nanyang profiles exhibit strong (mean ∼60 wt.% kaolinite) and extreme (mean ∼85 wt.% kaolinite) degrees of weathering, respectively. Our results show that light Mo isotopes are selectively retained in residual minerals, including kaolinite and hematite, whereas heavy Mo isotopes are preferentially leached out. Relative to the Mo-isotopic composition of the underlying unaltered parent basalt –0.38 ± 0.05 ‰ (2σ); vs. NIST 3134), the δ 98/95 Mo values of the overlying saprolite and surface soil at Penglai are modestly lower (–0.81 to –0.39‰) and higher (–0.35 to –0.12‰), respectively. In this profile, both δ 98/95 Mo and total organic carbon (TOC) decrease with depth, and their positive correlation in the soil layer ( r = +0.99, p(α) < 0.01, n = 6) implies that heavier Mo isotopes are fractionated into organic matter. In the more intensely weathered Nanyang profile, the δ 98/95 Mo of the underlying unaltered parent basalt is lower –0.56 ± 0.05‰ (2σ) than that at Penglai, and the weathered samples show a larger range of relatively lower values (–1.39 to –0.33‰), which may reflect adsorption of Mo by Fe oxides. Throughout the weathering profile, Fe2 O3 correlates positively with Mo concentration ( r = +0.86, p(α) < 0.01, n = 32) but negatively with δ 98/95 Mo ( r = –0.69, p(α) < 0.01, n = 32), implying that adsorption onto Fe-oxides played a key role in Mo mobility and isotopic fractionation. Extremely negative δ 98/95 Mo values (to –1.39‰) in the middle saprolite were likely linked to hydrothermal activity, as indicated by unusual enrichments of trace metals (Ni, Cu, Mo), low Hf/Y ratios, and a positive Eu/Eu* anomaly. Furthermore, the overlying soil layers of both profiles are characterized by enrichment of heavier Mo isotopes and higher Mo concentrations relative to their parent rocks. This may have been caused by additional inputs of Mo from atmospheric precipitation (average δ 98/95 Mo = +0.94 ± 0.14‰, 1σ, n = 3). Based on mass balance modeling of Mo isotopes and concentrations through the integrated profile, we infer Mo inputs from volcanic ash in the basalt-derived soils of northern Hainan Island. This study highlights the range of potential factors controlling Mo retention and isotopic fractionation as a function of variable weathering intensity, which may help to explain the large range of Mo isotopic compositions observed in river catchments at a global scale.